Penerapan Akuntansi Biaya Lingkungan di Rumah Sakit Hermana Lembean - Dengah, Dea Gratcia; Tirayoh, Victoria; Latjandu, Lady (Jurnal LPPM Bidang EkoSosBudKum (Ekonomi,Sosial,Budaya, dan Hukum), 2024)
Abstract: Environmental issues are increasingly interesting to be studied along with the development of technology and the world global economy. In the era of industrialization that emphasizes the use of technology as efficiently as possible, many companies ignore environmental aspects. For this reason, effective handling and planning related to the environment is needed. This study aims to find out how the application of environmental cost accounting in waste prevention efforts at Hermana Lembean Hospital. This research was conducted using a qualitative approach with a descriptive approach. Data analysis was conducted based on information related to environmental costs at Hermana Lembean Hospital. The data used comes from documentation or internal hospital data. The results of the study showed that Hermana Lembean Hospital had carried out good waste management which could be proven by the absence of external failure costs incurred by the hospital. With regard to the application of environmental cost accounting, the hospital has not implemented reporting specifically related to environmental cost accounting. This is evidenced by the absence of specific reports related to environmental costs. Keywords: Environmental Accounting, Environmental Costs, Hermana Lembean Hospital